A Study of Theme ‘Slavery’ in Buchi Emecheta’s Novel: The Slave Girl: Exploring Women's Roles and Slavery in Buchi Emecheta's 'The Slave Girl' (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Florence Onye Buchi Emecheta was a Nigerian born British novelist. Buchi Emecheta’s novels deal principally with the life experiences of Nigerian women, who are subordinated in an indigenous society deeply influenced by the western values introduced by British colonists. Emecheta who mainly writes about women, explores challenge women’s roles at great depth and traditional ideas of women’s activities in society. In the novel ‘The Slave Girl’, Emecheta turned our attention to the distinctive colour of existing and cultural networks of slavery in Africa at the turn of the century. With the mastery of language, she brings to life the story of OgbanjeOjebeta, and weak Ibuza girl sold to a wealthy aunt by her own brother. The novel illuminates strict and harsh treatment for weaker girls who are sold to domestic slaver. At the same time, it provides the rare and unique moments of humanity of perpetrators and victims. Ojebeta, a Nigerian woman who is sold into slavery in her own land after disease and tragedy leave her orphaned as a child. In her fellow slaves, she finds surrogate family that attaches together under the unbending will of their master. As Ojebeta becomes a woman and discovers her need for identity and freedom, her family and home, she realized that she would ultimately choose her destiny. However, throughout the novel we constantly remember the lack of woman value. In my view the slave girl stands as a strong indictment of cultural behaviours for women.